Effect of intermittent induced aeration on nitrogen removal and denitrifying-bacterial community structure in Cork and gravel vertical flow pilot-scale treatment wetlands - Aguilar, Lorena (2021)
Fil: Aguilara, Lorena. Universitat Politécnica de Catalunya; España